"Coming Out of My Shell": Motherleaders Contesting Fear, Vulnerability, and Despair through Family-focused Community Organizing. (30th March 2018) - Cossyleon, Jennifer E.
Women's political engagements often look different from those of men, and they are also undertheorized and understudied. The author examines how participation in family-focused community organizing shapes women's lives, self-perceptions, and relationships. Using 15 months of participant observations of organizing activities and 40 interviews with parent organizers the author calls motherleaders, the author demonstrates how family-focused community organizing shapes participants' lives in ways that help them leave "shells" of fear, vulnerability, and despair within their often marginalized lives as women of color, recent immigrants, and low-income mothers. The personal narratives of motherleaders demonstrate how their collective action transcends publicly stated formal organizational goals and powerfully affects them in life-altering ways. It is important that scholars seriously consider the intersecting identities of collective action participants, the meanings participants construct of and through "politics, " and the power of collective action to transform the lives of marginalized groups.